Upaya Pengembangan Wawasan Pelaku UMKM Terkait Digital Marketing Di Kelurahan Rungkut Kidul - Alvian priambudi; Muhammad Fajrul Yusuf Bahri; Erika Aprilia Renata; Listiana Anggraini; Vivin Amalia Dwi Vandini (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The aim of this study is to clarify and further develop UMKM’s view of digital marketing so that the efficiency and effectiveness of UMKM marketing can be achieved at maximum. This study will be beneficial for UMKM players to improve the quality and profitability of marketing through technology that facilitates consumer transactions. The results of this study are obtained from what is seen, felt, observed and questioned during the research process carried out by the research object. This research is a type of descriptive research that uses a qualitative approach. In this study, the researchers used two types of data: primary data and secondary data. Digital marketing or online marketing is a marketing strategy that uses electronic devices to present brands to consumers. The use of digital marketing is the most appropriate solution for UMKM to do online marketing and transactions. The presence of micro, small and medium-sized enterprises (UMKM) is one of the strengths of the Indonesian economy and the regional economy. At a time when the global economy and the Indonesian economy suffered a recession, the economic downturn had no negative impact on UMKM players, even most UMKM actors were still able to develop their efforts to support the country’s economy. Internet-based digital technology feels increasingly rapid development especially for users who can not get away from the internet, for example, Internet users who use social media as a marketing tool, marketplace, online store, etc. This research is expected to describe several issues related to the problems that will be discussed regarding the knowledge of the citizens of Rungkut Kidul on digital marketing and the use of e-commerce.